Instrument Connectivity in a Wireless MIMO Testbed - Pavel Loskot (1st Conference on Applied Radio Systems Research and Smart Wireless Communications, 2012)
A wireless multiple-input multiple-output (MIMO) testbed with up to $6$GHz RF carrier and up to 40MHz modulated signal bandwidth provides a unique opportunity for the real-time realistic experimentation, demonstration, testing, validation, general research&development as well as education of the telecommunication engineering. In this paper, the equipment connectivity and the corresponding interfaces of the testbed are discussed and compared such as the IEEE 488 (GPIB), IEEE 1394 (FireWire), IEEE 802.3 (Ethernet) and the USB. The emphasis is on the interface drivers that are available in Linux. Finally, a remote-controlled testbed operation is proposed as a new infrastructure-as a service paradigm in the test&measurement industry.